Audiovisual Translation: The Road Ahead - Nikolic, Kristijan; Bywood, Lindsay (Journal of Audiovisual Translation, 2021)
The audiovisual translation (AVT) sector has undergone rapid changes in recent years. It would be uncontroversial to state that the various stakeholders: academics; freelancers; technology providers, and language service providers (LSP) are likely to hold diverse and interesting views about what the future holds and how they might be called upon to adapt to recent and future changes. We have conducted qualitative research with representatives of these stakeholders in an attempt to ascertain their concerns and also their predictions for the future. Our motivation was to discover where stakeholders see the sector in the next 10 years. The research was conducted in 2016 and 2018 during the Languages and Media conference on a sample of 160 experts from various sector stakeholder groups. The findings show a broad range of issues that can be summarised into three main themes: the status of the language service provider; the need for standards and metrics; and the importance of training. Lay summary Audiovisual translation, or media translation such as subtitling and dubbing, has changed a great deal in recent years. Professionals involved in the creation of translations for television and film, which includes the ever-more popular platforms such as Netflix, are likely to have differing views on what the future holds for their industry, especially given the rising volume of translations made by machine translation systems which are then edited by human translators. We have conducted research among professionals involved in the audiovisual translation production process at a conference that takes place in Berlin every two years: Languages and the Media. This was an ideal place for such work since it attracts subtitlers, translators for dubbing, people who work in TV content translation, and trainers of media translators. We were hoping to discover the views of a wide range of people about what might happen in the short to medium term in the industry. The research was conducted in 2016 and 2018 among 160 professionals, such as subtitlers and employees of streaming platforms. The findings reveal some issues connected to translating for the media and point to the need for measuring translation quality and investing more resources into media translation training.